Συναισθηματική Εκφραστικότητα και Σχέσεις Συνομηλίκων σε Μαθητές Λυκείου - Μπελογιάννη, Βασιλική (Education Sciences, 2016)
This study examines the correlation between emotional self-expressiveness in family and peer relations. To assess the possible relationship between self-expressiveness and peer relations a random sample of 45 high school students filled out two self-report instruments, (a) the Self-Expressiveness in the Family for Children Questionnaire (SFEQ-Hel) (Halberstadt et al., 1995) and (b) the Inventory for Parents and Peers Attachment Questionnaire (IPPA- Peer version) (Armsden & Greenberg, 1987). In conclusion, it has been observed that there’s a high positive correlation between positive self-emotional expressiveness, trust and communication. On the contrary, negative self-expressiveness tends to correlate with higher scores of anger and alienation.